Liberalism and the postcolony : thinking the state in 20th-century Philippines - Claudio, Lisandro E. (Quezon City : Ateneo de Manila University Press, 2017)
"Extricating liberalism from the haze of anti-modernist and anti-European caricature, this book traces the role of liberal philosophy in the building of a new nation. It examines the role of toleration, rights, and mediation in the postcolony. Through the biographies of four Filipino scholar-bureaucrats--Camilo Osias, Salvador Araneta, Carlos P. Romulo, and Salvador P. Lopez--Lisandro E. Claudio argues that liberal thought served as the grammar of Filipino democracy in the 20th century. By looking at various articulations of liberalism in pedagogy, international affairs, economics, and literature, Claudio not only narrates an obscured history of the Philippine state, he also argues for a new liberalism rooted in the postcolonial experience"--
This book traces the role of liberal philosophy in the building of a new nation. Extricating liberalism from the haze of anti-modernist and anti-European caricature, it examines the role of toleration, rights, and mediation in the postcolony. Through the biographies of four Filipino scholar-bureaucrats--Camilo Osias, Salvador Araneta, Carlos P. Romulo, and Salvador P. Lopez--Lisandro E. Claudio argues that liberal thought served as the grammar of Filipino democracy in the 20th century. By looking at various articulations of liberalism in pedagogy, international affairs, economics, and literature, Claudio not only narrates an obscured history of the Philippine state, he also argues for a new liberalism rooted in the postcolonial experience.
Includes bibliographical references (pages [204]-220) and index.
300-399
Keywords: Liberalism -- Political aspects -- Philippines -- History -- 20th century; Philippines -- Politics and government -- 20th century